Rethinking antifascism : history, memory and politics, 1922 to the present - García, Hugo, 1975-; Yusta Rodrigo, Mercedes; Tabet, Xavier; Clímaco, Cristina, 1965- (Berghahn Books, 2016)
Bringing together leading scholars from a range of nations, Rethinking Antifascism provides a fascinating exploration of one of the most vibrant sub-disciplines within recent historiography. Through case studies that exemplify the field's breadth and sophistication, it examines antifascism in two distinct realms: after surveying the movement's remarkable diversity across nations and political cultures up to 1945, the volume assesses its postwar political and ideological salience, from its incorporation into Soviet state doctrine to its radical questioning by historians and politicians. Avoiding both heroic narratives and reflexive revisionism, these contributions offer nuanced perspectives on a movement that helped to shape the postwar world.